Characteristics associated with inflammatory breast cancer (IBC): An epidemiologic study from a dedicated IBC program. Issue 9 (1st September 2020) - White, Randie E.; Warren, Laura; Nakhlis, Faina; Rosenbluth, Jennifer; Bellon, Jennifer; Block, Caroline; Overmoyer, Beth
Abstract: There are scant data identifying epidemiologic characteristics among individuals diagnosed with inflammatory breast cancer (IBC), which is considered the most aggressive subtype of breast cancer. The purpose of this study was to evaluate the epidemiologic features among patients seen at a dedicated IBC program, to elucidate the potential causes of this disease and guide prevention strategies. We reviewed retrospective data from 447 patients enrolled in an IRB‐approved IBC registry through Dana‐Farber Cancer Institute from 1997 to 2016. The data examined included the following: demographics, medical, reproductive and family history, duration of symptoms prior to the diagnosis of IBC, pathologic characteristics, and clinical outcome. JMP statistical software was used to compile the data. Descriptive statistics were used to evaluate the data. The majority of patients (66.0%) were overweight or obese (body mass index [BMI] ≥ 25) at the time of diagnosis. Fifty patients (11.1%) had "secondary" IBC, defined as developing IBC after a previous history of non‐IBC breast cancer in an ipsilateral breast. Of those patients with secondary IBC, 60% were also overweight or obese at the time of IBC diagnosis. Approximately 58% of IBC patients had a family history of breast or ovarian cancer, including first‐ and second‐degree relatives. This analysis suggested a high frequency of familial breast/ovarian cancer among IBC patients which supports further evaluating genetic risks. This may have implications for screening and prevention strategies as well as insight into additional contributing risk factors. The prevalence of a high BMI among both pre‐ and postmenopausal women with IBC, including those diagnosed with secondary IBC, warrants focusing on strategies targeting the obesity crisis as a potential means of reducing the risk of developing this disease.